Bridging The Legitimacy Gap: A Multi-Level Governance Analysis of Geothermal Resistance in Pandarincang, Indonesia - Pratiwi, Diah Ayu; Arifin, Suherman; Rosita Wahyiah, Ita; Saputra, Dimas; Solihin, Muhammad (Jurnal EL-RIYASAH, 2025)
Geothermal energy is one of Indonesia's most promising renewable energy sources, particularly in areas along the Ring of Fire. However, managing geothermal energy often involves complex dynamics, including policy, governance, and local community resistance. This article aims to analyze the dynamics of geothermal energy policy governance in Indonesia, focusing on the case of Padarincang, Banten. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with stakeholders (central government, local government, and local communities), observation, and documentation from government reports, media, and academic publications. The research findings indicate that geothermal energy policy in Padarincang demonstrates a conflict of interests at various government levels (national, regional, and village) and non-state actors (investors, mass organizations, and civil society). Community resistance arises due to weak participation mechanisms and a lack of communication between governance levels. This study emphasizes that the success of Indonesia's energy transition is highly dependent on strengthening collaborative governance across all levels and actors.